Nifty after fifty: evaluation of a physical activity directory for older people - Ruth Miller; Yvette D. Miller (Elsevier, 2003)
Abstract Objective: To develop a physical activity directory (PAD) for Brisbane people over the age of 50 years for distribution by two methods (given or requested), and to determine its effectiveness in raising awareness and encouraging older people to participate in local physical activity options. Methods: Baseline demographic data and stage of change was collected from 224 participants who received the directory. Participants were interviewed by telephone six weeks later to determine their use of the directory on a number of dimensions. Results: Most participants interviewed at follow‐up remembered reading the directory. Participants who requested the directory were significantly more likely than those who were given it to: be contemplators, read the directory, plan to ring a number, plan to attend a class, and to share the directory with others. Participants who were contemplators were significantly more likely to have participated in physical activity of their own and rang a number from the directory. The directory increased over half the participants' awareness of local physical activity options, yet only 7% reported ringing a number and 15% reported doing their own physical activity. Conclusions: The directory was more effective in raising awareness about physical activity options than encouraging people to participate in physical activity, and participants with short‐term plans to be more active were more likely to have used the directory. Implications: The directory, even when linked with other services, raises awareness about physical activity options, but has minimal short‐term influence on participation.